1998
DOI: 10.2166/wst.1998.0405
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide and metal pollution by urban snowmelt: impact of deicing compounds

Abstract: Highway and road deicing operations provide traffic safety during winter driving conditions in snowbelt areas. Using large quantities of deicing chemicals causes water quality problems that need to be addressed and remediated. Two specific problems are discussed, i.e., presence of cyanides in deicing salt and decreased partitioning of metals in snowmelt resulting from high salt concentrations. Complex ferrocyanide compounds are added to salt to prevent caking. By photodecomposition, these cyanides can be broke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…Therefore, a much higher dosage of the anticaking agent, up to 75 ppm for ferrocyanide, is required in deicing salt (road salt), raising concerns about damage to the environment. 8 The lower effectiveness of the anticaking agents is likely linked to the formation of sodium chloride dihydrate, NaCl· 2H 2 O, or hydrohalite, which is a stable form of sodium chloride in the presence of water at temperatures below 0.1°C 9 (see the phase diagram in Figure 1). This dihydrate form of sodium chloride has been studied surprisingly little.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, a much higher dosage of the anticaking agent, up to 75 ppm for ferrocyanide, is required in deicing salt (road salt), raising concerns about damage to the environment. 8 The lower effectiveness of the anticaking agents is likely linked to the formation of sodium chloride dihydrate, NaCl· 2H 2 O, or hydrohalite, which is a stable form of sodium chloride in the presence of water at temperatures below 0.1°C 9 (see the phase diagram in Figure 1). This dihydrate form of sodium chloride has been studied surprisingly little.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This degradation occurs when salt dissociates in water at pH <8 and Eh greater than −600 mV. Fortunately, natural waters scarcely show both high alkalinity and low redox potential values (Novotny et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Westerlund et al (2003) found that in Luleå, Sweden, metal elements are more particulate bound during the snowmelt period than during the rain period, when they are characterized by a higher percentage of dissolved fractions. Using salt as de-icer results in an increase in the dissolved metals in salt-laden snowmelt and, consequently, in an increase in toxicity (Novotny et al, 1998).…”
Section: Introductionmentioning
confidence: 99%